Ultra-High Electromagnetic Absorption Property of One-Dimensional Carbon-Supported Ni/Mo2C and Polyvinylidene Fluoride - Gao, Shan; Feng, Jie; Wang, Guang-Sheng; Liang, Ben-Liang (Frontiers in Chemistry, 2019)
A novel one-dimensional carbon-supported Ni/Mo2C (Ni/Mo2C-C) nanocomposite with excellent electromagnetic wave absorption properties was successfully synthesized by annealing NiMoO4@PDA directly, and then the (Ni/Mo2C-C) /polyvinylidene fluoride (PVDF) composites were fabricated using a simple blending and hot-moulding technique. An excellent reflection loss (RL) of -55.91 dB at 9.28 GHz with a low filler loading (15 wt%) and effective bandwidth (RL < -10 dB) of 14.12 GHz in the thickness range of 1.5 - 5.0 mm was obtained. Dielectric loss is considered to be the dominant mechanism of (Ni/Mo2C-C)/PVDF, which was confirmed by the Debye relaxation process and attenuation theory.